Long-Term Effects of Adjuvant Intravitreal Treatment with Autologous Bone Marrow-Derived Lineage-Negative Cells in Retinitis Pigmentosa - Marta P. Wiącek; Wojciech Gosławski; Aleksandra Grabowicz; Anna Sobuś; Miłosz P. Kawa; Bartłomiej Baumert; Edyta Paczkowska; Sławomir Milczarek; Bogumiła Osękowska; Krzysztof Safranow; Alicja Zawiślak; Wojciech Lubiński; et al. (Stem Cells International)
Background. Autologous bone marrow-derived lineage-negative (Lin−) cells present antiapoptotic and neuroprotective activity. The aim of the study was to evaluate the safety and efficacy of novel autologous Lin− cell therapy during a 12-month follow-up period. Methods. Intravitreal injection of Lin− cells in 30 eyes with retinitis pigmentosa (RP) was performed. The fellow eyes (FEs) were considered control eyes. Functional and morphological eye examinations were performed before and 1, 3, 6, 9, and 12 months after the injection. Results. Patients whose symptoms started less than 10 years ago gained 14±10 letters, while those with a longer disease duration gained 2.86±8.54 letters compared to baseline at the 12-month follow-up (p=0.021). There were significantly higher differences in response densities of P1-wave amplitudes in the first ring of multifocal ERGs in treated eyes than FE recordings in all follow-up points were detected. Accordingly, the mean deviation in 10-2 static perimetry improved significantly in the treated eyes compared with fellow eyes 12 months after the procedure. The QoL scores improved significantly and lasted until the 9-month visit. Conclusion. Lin− cell-based therapy is safe and effective, especially for a well-selected group of RP patients who still maintained good function of the foveal cones.